2006
DOI: 10.1186/1741-7007-4-22
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mammalian GPCRs in C. elegansgenerates novel behavioural responses to human ligands

Abstract: Background: G-protein-coupled receptors (GPCRs) play a crucial role in many biological processes and represent a major class of drug targets. However, purification of GPCRs for biochemical study is difficult and current methods of studying receptor-ligand interactions involve in vitro systems. Caenorhabditis elegans is a soil-dwelling, bacteria-feeding nematode that uses GPCRs expressed in chemosensory neurons to detect bacteria and environmental compounds, making this an ideal system for studying in vivo GPCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Pharmacological profiling of parasite GPCRs in this heterologous system requires that the receptors are properly folded and exported to the membrane, that they signal through endogenous G proteins, and that their activation in response to exogenous ligands can be measured through convenient phenotypic endpoints. Building on previous work leveraging C. elegans as a heterologous expression platform for the expression of human GPCRs ( 79 , 80 ) and anthelmintic targets ( 35 , 61 63 ), we first established transgenic lines expressing Bma- GAR-3 in the C. elegans ASH sensory amphid neuron and the body wall muscle. These parasitized C. elegans strains were used to develop and optimize tissue-specific assays to measure receptor activation.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological profiling of parasite GPCRs in this heterologous system requires that the receptors are properly folded and exported to the membrane, that they signal through endogenous G proteins, and that their activation in response to exogenous ligands can be measured through convenient phenotypic endpoints. Building on previous work leveraging C. elegans as a heterologous expression platform for the expression of human GPCRs ( 79 , 80 ) and anthelmintic targets ( 35 , 61 63 ), we first established transgenic lines expressing Bma- GAR-3 in the C. elegans ASH sensory amphid neuron and the body wall muscle. These parasitized C. elegans strains were used to develop and optimize tissue-specific assays to measure receptor activation.…”
Section: Resultsmentioning
confidence: 99%
“…An unusual feature of these neurons is that they are often polymodal and can respond to distinct types of stimuli. C. elegans sensory neurons can express multiple GPCRs in the same nerve cell, allowing the nematode to respond specifically to different environmental conditions using only a few neurons [37] . For this reason, one would expect that mutations in genes encoding proteins involved in a wide range of interaction mechanisms between nerve cells should cause defects in numerous behavioral responses.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have been limited to C. elegans ' native chemo‐sensation repertoire. Interestingly, however, Teng et al (2006) showed how expression of mammalian GPCRs in gustatory neurons enabled C. elegans to detect and respond to previously undetected stimuli. The expression of mouse Sstr2 and human CCR5 in nociceptive neurons evoked avoidance behavior in response to somatostatin and MIP‐1α.…”
Section: Advances In Nematode Synthetic Biologymentioning
confidence: 99%